Smart Motor Driver System for Speed and Position Control of a DC Geared Motor - Zulkurnain, Zulmukhris Hazazi (Universiti Teknologi PETRONAS, 2016)
Applications of DC motor control are important and widely used in various area of industries. Generally, the motor controller is developed to control the performance of DC motor. The speed and direction of the motor can be controlled from given input at the controller. Majority of DC motor controller in market today utilize separate circuits for the controller and motor driver. This project is carried out to design and implement an integrated controller and motor driver in a single platform. By integrating the both circuits in a single platform, it may prevent compatibility issues and increase system development in the area of DC motor control. Normally, the motor rotates continuously in clockwise and anticlockwise position. In this project, the focus is to rotate the motor to a specified position at the desired speed of given input by implementing a control system within the motor controller.